(untitled) (International Journal of Pharmaceutical and Life Sciences, 2012)
We have done research work in lab to find out proper formulation of immediate release tablet by using of various types of disintegrants (crospovidone, sodium starch glycolate and sodium carboxymethylcellulose), in order to examine the effect of mode of absorption of disintegrants on release mechanism from tablets. Acetaminophen, a poor soluble drug was used as a model drug to estimate its release pattern from different formulations. The USP paddle method was selected to perform the dissolution profiles carried out by USP apparatus 2 (paddle) at 50 rpm in 900 ml phosphate buffer pH 5.8. Successive dissolution time, time required for 25%, 50% and 80% of the drug release (T25%, T50%, T80%) was used to evaluate the dissolution results. A One way analysis of variance (ANOVA) was used to recognize the result. Statistically significant differences were found among the drug release profile from all the formulations except mode of addition of crosspovidone. At a fixed amount of disintegrants, extragranular mode of addition seemed to be the best mode of incorporation. The best release was achieved with the sodium carboxymethylcellulose and sodium starch glycolate containing formulations. The T50 and T80 values were analytical of the fact that the drug release was faster from tablet formulations containing carboxymethylcellulose and sodium starch glycolate. The drug release was very much negligible difference by the mode of crospovidone addition. Two formulations found very small T50 and T80 values indicating very much faster release. From the all formulations corresponded extragranular mode of addition could be the best mode of incorporation. The drug release was unaffected by the mode of crospovidone addition. The mode of incorporation of disintegrants suggested enchancing the release of poor soluble drugs. DOI: http://dx.doi.org/10.3329/ijpls.v1i3.12979 International Journal of Pharmaceutical and Life Sciences Vol.1(3) 2012